Religion in the media: a linguistic analysis - Al-Azami, A. Salman (Palgrave Macmillan, 2016)
Dedication -- Preface -- Acknowledgments -- Contents -- 1: Introduction-Language, Religion, and Media: A New Approach -- Religion and the Media -- Language and the Media -- Language and Religion -- Audience Response Studies -- Media Representation: The Three Abrahamic Religions -- Terminologies in the Book -- New Approaches in Methodology -- Media Characteristics and Media Discourse -- Literature Review -- Religion, Media, and Culture -- Religion in Films -- Language and the Media -- Language and Religion -- Language, Religion, and the Media -- Audience Response Study -- Representation of the Three Religions -- Islam -- Christianity -- Judaism -- Scope of the Study -- Chapters in the Book -- 2: Media Representation of Religions: A Critical Discourse Analysis -- Discourse Analysis -- Critical Discourse Analysis -- Media Discourse -- Critical Discourse Analysis of Religions in the Media -- News Reporting -- Islam -- Christianity -- Judaism -- TV Documentaries -- Fictional Representations -- Representation of Islam -- Representation of Christianity -- Representation of Judaism -- 3: Media Representation: Audience Response -- Audience Response Study -- The Encoding/Decoding Model -- Innovative Aspects of This Study -- Methodology -- Focus Group Meetings -- The Participants -- Muslims -- Manchester -- London -- Birmingham -- Christians -- Manchester -- Birmingham -- London -- Non-Religious -- Manchester -- Liverpool -- Lack of Jewish Participation -- Hypotheses -- Hypothesis 1 -- Hypothesis 2 -- Hypothesis 3 -- Hypothesis 4 -- Hypothesis 5 -- Findings -- Muslim Audience: Rejecting Media Portrayals of Islam -- Why and How the Media Portray Islam Negatively -- Religion in General Marginalised -- Segregation of Islam Blown Out of Proportion -- Islam Treated Unfairly Compared to Other Religions -- Comments on Other Religions -- Self-Critical on Muslims.